Run-flat tire inner surface rubber and preparation method thereof

By using specific components in the inner surface glue of the air-deficient tire, the existing problems of insufficient bending performance and modulus and high heat generation are solved, and better air tightness and mileage are achieved.

CN119798878APending Publication Date: 2025-04-11SICHUAN YUANXING RUBBER CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510039362.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The flexural performance and modulus of the inner surface glue of the existing air-deficient tires are insufficient, and the heat generation is high, which affects the air-tightness and mileage.

Method used

The components such as brominated butyl rubber, low styrene styrene butadiene rubber, epoxy rubber, nanocarbon materials, carbon black, zinc oxide, stearic acid, tackifier, uniformizer, crosslinking agent and accelerator are prepared by mixing to improve the modulus and flexural performance of the glue.

Benefits of technology

It significantly improves the airtightness, durability and fatigue resistance of the tire, reduces the heat generation ability, and extends the tire's continuous mileage in the absence of air.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses run-flat tire inner surface rubber and a preparation method thereof, and relates to the technical field of tire manufacturing. The run-flat tire inner surface rubber is prepared from the following components in parts by weight: 30 to 50 parts of brominated butyl rubber, 30 to 40 parts of low styrene butadiene rubber, 10 to 20 parts of epoxy rubber, 20 to 40 parts of nano carbon material, 30 to 50 parts of carbon black, 2 to 5 parts of zinc oxide, 1 to 3 parts of stearic acid, 2 to 5 parts of tackifier, 1 to 2 parts of homogenizing agent, 0.5 to 1 part of cross-linking agent and 1.4 to 2 parts of accelerant. The inner surface rubber disclosed by the invention has good mechanical properties, can greatly improve the modulus and flexural property of a rubber material, is small in hysteresis loss so as to reduce the heat generation property, and has excellent wear resistance and aging resistance, so that the puncture-proof effect of a tire is enhanced, and the inner surface rubber has better air tightness and is suitable for popularization and application. Therefore, the run-flat tire has enough continuous mileage under the condition of air shortage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of tire manufacturing, and in particular to an inner rubber of a run-flat tire and a preparation method thereof. Background Art

[0002] Run-flat tires are also called explosion-proof tires. Even when the tires are deflated or even have zero tire pressure, they can still rely on their hard tire sidewalls to support the vehicle to travel normally for a considerable distance. Once a tire leaks air while driving at high speed, the tire pressure will decrease, and the car will inevitably lose balance and be unable to drive normally and control the direction. Therefore, under this situation, research on run-flat tires has been gradually carried out. When a run-flat tire is deflated or even loses air pressure during driving, the entire vehicle is mainly supported by the inner rubber of the tire sidewall to continue driving for a distance. Therefore, the inner rubber becomes a key part of the performance of the run-flat tire. However, the flexural performance and modulus of the traditional inner rubber need to be improved, and it has a high heat generation, which has a great impact on the air tightness of the run-flat tire, reducing the mileage of the tire when it is deflated. Summary of the invention

[0003] The main purpose of the present application is to provide a run-flat tire inner rubber and a preparation method thereof, aiming to solve the technical problem that the performance of the existing run-flat tire inner rubber needs to be improved.

[0004] To achieve the above-mentioned purpose, the present application proposes a run-flat tire inner rubber, which comprises the following components by weight:

[0005] 30-50 parts of brominated butyl rubber, 30-40 parts of low styrene styrene butadiene rubber, 10-20 parts of epoxy rubber, 20-40 parts of nano-carbon material, 30-50 parts of carbon black, 2-5 parts of zinc oxide, 1-3 parts of stearic acid, 2-5 parts of tackifier, 1-2 parts of homogenizer, 0.5-1 parts of cross-linking agent and 1.4-2 parts of accelerator.

[0006] Optionally, the components include, by weight:

[0007] 40 parts of brominated butyl rubber, 35 parts of low styrene butadiene rubber, 15 parts of epoxy rubber, 30 parts of nano carbon material, 40 parts of carbon black, 4 parts of zinc oxide, 2 parts of stearic acid, 3 parts of tackifier, 2 parts of homogenizer, 0.8 parts of crosslinking agent and 1.8 parts of accelerator.

[0008] Optionally, the component further comprises 0.5 to 1 part of alkylphenol disulfide by weight.

[0009] Optionally, the tackifier is one of C5 resin and C9 resin.

[0010] Optionally, the homogenizer is a mixture of one or more of RH100, CJ400 and JJHM40.

[0011] Optionally, the cross-linking agent is one of sulfur and insoluble sulfur or a mixture of the two.

[0012] Optionally, the accelerator includes thiazole compounds and thiuram compounds.

[0013] The present application also proposes a method for preparing the inner rubber of a run-flat tire, comprising the following steps:

[0014] The epoxy rubber is plasticized and then mixed with brominated butyl rubber, stearic acid, a tackifier and a homogenizer, and then nano carbon material and carbon black are added and mixed, and after rubber removal, a stage A rubber is obtained;

[0015] The A-stage rubber is mixed with low-styrene styrene-butadiene rubber, zinc oxide, an accelerator, a crosslinking agent and alkylated disulfide, and after the rubber is discharged, a finished inner surface rubber is obtained.

[0016] Optionally, the step of plasticizing the epoxy rubber, mixing it with brominated butyl rubber, stearic acid, a tackifier and a homogenizer, adding nano-carbon material and carbon black for mixing, and obtaining the A-stage rubber after rubber removal comprises:

[0017] After plasticizing the epoxy rubber, put it into an internal mixer together with brominated butyl rubber, stearic acid, tackifier and homogenizer for mixing for 22s-28s, then put in nano-carbon material and carbon black and mix to 85℃-95℃, lift the top plug and clean to 100℃-105℃, then press the top plug, when the mixing temperature reaches 142℃-148℃, lift the top plug, open the lower top plug to discharge the rubber, and cool to room temperature to obtain stage A rubber.

[0018] Optionally, the step of mixing the stage A rubber with low styrene butadiene rubber, zinc oxide, an accelerator, a crosslinking agent and an alkylated disulfide, and obtaining a finished inner rubber after degumming, comprises:

[0019] The stage A rubber is put into an internal mixer together with low styrene butadiene rubber, zinc oxide, accelerator, crosslinking agent and alkylated disulfide. When the mixing temperature reaches 75°C-85°C, the top plug is lifted for cleaning and then the top plug is pressed. When the mixing temperature reaches 95°C-105°C, the top plug is lifted and the lower top plug is opened for rubber discharge. After cooling to room temperature, a finished inner rubber is obtained.

[0020] This application includes at least the following beneficial effects:

[0021] The inner rubber of the present application is prepared by mixing brominated butyl rubber, low styrene butadiene rubber, epoxy rubber, nano-carbon material, carbon black, zinc oxide, stearic acid, tackifier, leveler, cross-linking agent and accelerator as raw materials. The brominated butyl rubber has excellent anti-aging and high temperature resistance properties, and can also provide excellent air tightness for the tire, ensuring that the tire maintains a low air pressure loss rate during long-term use; low styrene butadiene rubber provides the tire with better mechanical properties, wear resistance and certain heat resistance, thereby reducing the heat generation of the tire and ensuring the long-term stability of the tire; epoxy rubber is natural rubber that has been epoxidized to have better tear resistance and high modulus, which can provide support performance for the inner rubber and avoid the problem of air tightness of the tire due to the addition of natural rubber in the tire rubber compound in the prior art. In order to solve the problem of negative impact on the performance of tires, the combined use of brominated butyl rubber, low styrene butadiene rubber and epoxy rubber can improve the overall performance of tires, ensure air tightness, durability and fatigue resistance; nano-carbon materials have excellent thermal conductivity and can reduce the heat generation of tires; carbon black can be used as a filler to enable tires to obtain lower heat generation performance; tackifiers can improve the fluidity and processing performance of rubber compounds; homogenizers can ensure the uniform mixing of other ingredients in the rubber compound, thereby improving the mixing processing performance; cross-linking agents can ensure the cross-linking density of rubber and improve the heat aging resistance of rubber; accelerators can promote the rate of vulcanization reaction and optimize the processing and vulcanization process of rubber; zinc oxide and stearic acid can be used as rubber activators. Zinc oxide and stearic acid react to generate highly active zinc stearate, which can improve the activity of the accelerator and further promote the rapid completion of the cross-linking process of rubber. Through the coordinated use of the components in the present application, the inner rubber of the present application has good mechanical properties, can greatly improve the modulus and flexural properties of the rubber, and has small hysteresis loss to reduce heat generation, while having excellent wear resistance and aging resistance, thereby enhancing the anti-puncture effect of the tire, and has better air tightness, so that the run-flat tire has sufficient mileage when it is deflated. DETAILED DESCRIPTION

[0022] The technical solution of the present application will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.

[0023] In view of the technical problems existing in the prior art, the embodiment of the present application provides an inner rubber of a run-flat tire, which comprises the following components by weight:

[0024] 30-50 parts of brominated butyl rubber, 30-40 parts of low styrene styrene butadiene rubber, 10-20 parts of epoxy rubber, 20-40 parts of nano-carbon material, 30-50 parts of carbon black, 2-5 parts of zinc oxide, 1-3 parts of stearic acid, 2-5 parts of tackifier, 1-2 parts of homogenizer, 0.5-1 parts of cross-linking agent and 1.4-2 parts of accelerator.

[0025] The inner rubber of the present application is prepared by mixing brominated butyl rubber, low styrene butadiene styrene rubber, epoxy rubber, nano-carbon material, carbon black, zinc oxide, stearic acid, tackifier, leveler, cross-linking agent and accelerator as raw materials. The brominated butyl rubber has excellent anti-aging and high temperature resistance properties, and can also provide excellent air tightness for the tire, ensuring that the tire maintains a low air pressure loss rate during long-term use; low styrene butadiene styrene rubber provides the tire with better mechanical properties, wear resistance and certain heat resistance, thereby reducing the heat generation of the tire and ensuring the long-term use stability of the tire; epoxy rubber is natural rubber that has been epoxidized to give it better tear resistance and high modulus, which can provide supporting performance for the inner rubber, and at the same time can avoid the problem of negative impact on the air tightness of the tire due to the addition of natural rubber in the tire rubber compound in the prior art. The combined use of brominated butyl rubber, low styrene butadiene styrene rubber and epoxy rubber can improve the tire's Overall performance, ensuring air tightness, durability and fatigue resistance; nano-carbon materials have excellent thermal conductivity and can reduce the heat generation of tires; carbon black can be used as a filler to enable the tire to obtain lower heat generation performance, and the amount of carbon black should not be too high. Too high will lead to difficulty in dispersion, and the hardness of the rubber is too high, which is not good for flexural resistance. Too low an amount will lead to poor reinforcement, resulting in insufficient strength and hardness of the inner rubber, which is not good for rigidity. Therefore, this application controls the weight of carbon black to be 30-50 parts; the tackifier can improve the fluidity and processing performance of the rubber; the homogenizer can ensure the uniform mixing of other ingredients in the rubber, thereby improving the mixing processing performance; the cross-linking agent can ensure the cross-linking density of the rubber and improve the heat aging resistance of the rubber; the accelerator can promote the rate of vulcanization reaction and optimize the processing and vulcanization process of the rubber; zinc oxide and stearic acid can be used as rubber activators. Zinc oxide and stearic acid react to generate highly active zinc stearate, which can increase the activity of the accelerator and further promote the rapid completion of the cross-linking process of the rubber. Through the coordinated use of the components in the present application, the inner rubber of the present application has good mechanical properties, can greatly improve the modulus and flexural properties of the rubber, and has small hysteresis loss to reduce heat generation, while having excellent wear resistance and aging resistance, thereby enhancing the anti-puncture effect of the tire, and has better air tightness, so that the run-flat tire has sufficient mileage when it is deflated.

[0026] As an implementation method of the present application, the components include, by weight:

[0027] 40 parts of brominated butyl rubber, 35 parts of low styrene butadiene rubber, 15 parts of epoxy rubber, 30 parts of nano carbon material, 40 parts of carbon black, 4 parts of zinc oxide, 2 parts of stearic acid, 3 parts of tackifier, 2 parts of homogenizer, 0.8 parts of crosslinking agent and 1.8 parts of accelerator.

[0028] Specifically, the brominated butyl rubber of the present application is Exxon's 3745 brand, which has low heat generation and good gas retention performance; the low styrene butadiene rubber adopts LG's solution-polymerized butadiene F1038, which has low heat generation, good fatigue resistance and good gas retention; the nano-carbon material is the SG06 material of the Southern Graphite Research Institute, which has excellent air tightness, excellent thermal conductivity and low heat generation; the carbon black brand is carbon black N660.

[0029] As an embodiment of the present application, the components further include 0.5-1 parts of alkylphenol disulfide by weight. Alkylphenol disulfide has a strong vulcanization-promoting effect, which can improve the production efficiency of rubber by accelerating the rate of vulcanization reaction, significantly reduce the vulcanization time in the high-temperature vulcanization process, and help to quickly complete the cross-linking process of rubber, and the acceleration of the vulcanization reaction optimizes the elasticity, hardness and other properties of the rubber, and alkylphenol disulfide can also improve the wear resistance and mechanical strength of the rubber by enhancing the cross-linking degree of low styrene butadiene rubber and epoxy rubber molecular chains, and the inner rubber of the present application is more resistant to friction during use through this cross-linking effect, thereby extending the service life of the tire.

[0030] As an implementation method of the present application, the tackifier is one of C5 resin and C9 resin.

[0031] Specifically, the present application adopts resin as a tackifier, and selects C5 resin and C9 resin. C5 resin is a resin with a chemical structure composed of 5 carbon atoms, which is usually obtained through processes such as petroleum cracking and catalytic polymerization. C5 resin has a lower viscosity and can effectively reduce the viscosity of rubber during mixing, improve the fluidity and processing properties of the rubber, and improve the wear resistance of the rubber, thereby enhancing the service life of the tire; C9 resin is a resin composed of 9 carbon atoms, which is usually obtained through polymerization reactions of aromatic hydrocarbons (such as benzene, toluene, xylene, etc.). C9 resin has good high-temperature stability, which can enable the tire rubber to maintain good mechanical properties under high temperature environments, and effectively improve the rigidity and hardness of the rubber.

[0032] As an implementable embodiment of the present application, the homogenizer is a mixture of one or more of RH100, CJ400 and JJHM40.

[0033] The homogenizer can improve the dispersion and uniformity of the rubber compound, ensure the uniform mixing of other components in the application in the rubber compound, thereby improving the mixing processing performance, optimizing the physical properties and stability of the rubber compound, and helping to improve the overall quality and performance of the tire. The homogenizer brands selected in this application are RH100, CJ400 and JJHM40.

[0034] As an implementation method of the present application, the crosslinking agent is one of sulfur and insoluble sulfur or a mixture of the two. The crosslinking agent of the present application is selected from sulfur and insoluble sulfur with high thermal stability, which can ensure the crosslinking density of the rubber, improve the heat aging resistance of the rubber, and reduce dynamic heat generation.

[0035] As an implementation method of the present application, the accelerator includes thiazole compounds and thiuram compounds.

[0036] Specifically, the accelerators may be N,N'-dibenzothiazole disulfide (accelerator DM) and N-dicyclohexyl-2-benzothiazole-2-sulfur (accelerator TT). Accelerator TT promotes the vulcanization reaction at a relatively mild rate. Its combination with accelerator DM can achieve a balanced effect, optimize the processing and vulcanization process of rubber, accelerate vulcanization at a lower temperature, help improve the hardness, wear resistance and tensile strength of the rubber, and improve the physical properties and thermal stability of the rubber.

[0037] The embodiment of the present application also provides a method for preparing the inner rubber of a run-flat tire, comprising the following steps:

[0038] The epoxy rubber is plasticized and then mixed with brominated butyl rubber, stearic acid, a tackifier and a homogenizer, and then nano carbon material and carbon black are added and mixed, and after rubber removal, a stage A rubber is obtained;

[0039] The A-stage rubber is mixed with low-styrene styrene-butadiene rubber, zinc oxide, an accelerator, a crosslinking agent and alkylated disulfide, and after the rubber is discharged, a finished inner surface rubber is obtained.

[0040] The present application precisely controls the mixing process so that the inner rubber obtained after mixing can maintain good elasticity while having multiple excellent properties such as high strength, high modulus, excellent tear resistance, flexural performance and support performance, thereby ensuring the stability and safety of the tire when running in an under-inflation environment.

[0041] As an implementation method of the present application, the epoxy rubber is plasticized and then mixed with brominated butyl rubber, stearic acid, a tackifier and a homogenizer, and then nano-carbon material and carbon black are added and mixed, and after the rubber is discharged, the step of obtaining the A-stage rubber includes:

[0042] After plasticizing the epoxy rubber, put it into an internal mixer together with brominated butyl rubber, stearic acid, tackifier and homogenizer for mixing for 22s-28s, then put in nano-carbon material and carbon black and mix to 85℃-95℃, lift the top plug and clean to 100℃-105℃, then press the top plug, when the mixing temperature reaches 142℃-148℃, lift the top plug, open the lower top plug to discharge the rubber, and cool to room temperature to obtain stage A rubber.

[0043] As an implementation method of the present application, the step of mixing the A-stage rubber with low styrene butadiene rubber, zinc oxide, an accelerator, a crosslinking agent and an alkylated disulfide, and obtaining a finished inner rubber after the rubber is discharged, comprises:

[0044] The stage A rubber is put into an internal mixer together with low styrene butadiene rubber, zinc oxide, accelerator, crosslinking agent and alkylated disulfide. When the mixing temperature reaches 75°C-85°C, the top plug is lifted for cleaning and then the top plug is pressed. When the mixing temperature reaches 95°C-105°C, the top plug is lifted and the lower top plug is opened for rubber discharge. After cooling to room temperature, a finished inner rubber is obtained.

[0045] Specifically, the internal mixer of the present application adopts F270 equipment, wherein the machine speed of the A-stage rubber mixing machine is 50r / min, and the machine speed of the finished product inner rubber mixing machine is 25r / min.

[0046] The above technical solution of the present application is described in detail below in conjunction with specific embodiments.

[0047] Example 1

[0048] A method for preparing an inner rubber of a run-flat tire comprises the following steps:

[0049] 20g of epoxy rubber was plasticized and put into an internal mixer together with 50g of brominated butyl rubber 3745, 2g of stearic acid, 3g of C5 resin and 2g of RH100 for mixing for 25s. Then 30g of nano carbon material SG06 and 40g of carbon black N660 were added and mixed to 90°C. The top plug was lifted and cleaned to 105°C, and the top plug was pressed again. When the mixing temperature reached 145°C, the top plug was lifted and the bottom plug was opened to discharge the glue. After standing for 4h and cooling to room temperature, stage A glue was obtained.

[0050] The stage A rubber, 30 g of low styrene butadiene rubber F1038, 4 g of zinc oxide, 1.2 g of accelerator DM, 0.2 g of accelerator TT, 0.9 g of sulfur and 0.8 g of alkylphenol disulfide were put into an internal mixer. When the mixture was mixed to 80° C., the top plug was lifted for cleaning and then pressed. When the mixing temperature reached 100° C., the top plug was lifted and the bottom plug was opened for rubber removal. After cooling to room temperature, a finished inner rubber was obtained.

[0051] The inner rubber performance test was carried out in accordance with the provisions of GB / T 30196-2013 Self-supporting Run-Flat Tire. After testing, the inner rubber dispersion grade was 8.6, the hardness was 70HA, there was no crack after 1.45 million fatigue tests, and the air permeability coefficient was 5.82×10 -14 m 2 ·s -1 The static pressure difference loss is within 3.16% / month, the compression heat generation is 20°C, and the compression deformation rate is 0.8%; after the inner rubber is applied to the tire, it can continue to travel 980 kilometers when the tire pressure is 0.

[0052] Example 2

[0053] A method for preparing an inner rubber of a run-flat tire comprises the following steps:

[0054] 10g of epoxy rubber was plasticized and put into an internal mixer together with 40g of bromobutyl rubber 3745, 2g of stearic acid, 3g of C5 resin and 2g of RH100 for mixing for 27s. Then 35g of nanocarbon material SG06 and 35g of carbon black N660 were added and mixed to 85°C. The top plug was lifted and cleaned to 100°C, and the top plug was pressed again. When the mixing temperature reached 142°C, the top plug was lifted and the bottom plug was opened to discharge the glue. After standing for 4h and cooling to room temperature, the A-stage glue was obtained.

[0055] The stage A rubber, 50 g of low styrene butadiene rubber F1038, 4 g of zinc oxide, 1.2 g of accelerator DM, 0.2 g of accelerator TT, 0.9 g of sulfur and 0.8 g of alkylphenol disulfide were put into an internal mixer. When the mixture was mixed to 75° C., the top plug was lifted for cleaning and then pressed. When the mixing temperature reached 95° C., the top plug was lifted and the bottom plug was opened for rubber removal. After cooling to room temperature, a finished inner rubber was obtained.

[0056] The inner rubber performance test was carried out in accordance with the provisions of GB / T 30196-2013 Self-supporting Run-Flat Tire. After testing, the inner rubber dispersion grade was 8.8, the hardness was 71HA, there was no crack after 1.45 million fatigue tests, and the air permeability coefficient was 5.52×10 -14 m 2 ·s -1 The static pressure difference loss is within 3.56% / month, the compression heat generation is 21°C, and the compression deformation rate is 0.9%; after the inner rubber is applied to the tire, it can continue to travel 930 kilometers when the tire pressure is 0.

[0057] Example 3

[0058] A method for preparing an inner rubber of a run-flat tire comprises the following steps:

[0059] 15g of epoxy rubber was plasticized and put into an internal mixer together with 40g of brominated butyl rubber 3745, 2g of stearic acid, 3g of carbon nine resin and 2g of CJ400 for mixing for 27s. Then 30g of nano carbon material SG06 and 40g of carbon black N660 were added and mixed to 95°C. The top plug was lifted and cleaned to 105°C, and the top plug was pressed again. When the mixing temperature reached 148°C, the top plug was lifted and the bottom plug was opened to discharge the glue. After standing for 4h to cool to room temperature, the A-stage glue was obtained.

[0060] The stage A rubber, 35 g of low styrene butadiene rubber F1038, 4 g of zinc oxide, 1.4 g of accelerator DM, 0.4 g of accelerator TT, 0.8 g of insoluble sulfur and 0.8 g of alkylphenol disulfide were put into an internal mixer. When the mixing temperature reached 85° C., the top plug was lifted for cleaning and then pressed. When the mixing temperature reached 105° C., the top plug was lifted and the bottom plug was opened for rubber removal. After cooling to room temperature, a finished inner rubber was obtained.

[0061] The inner rubber performance test was carried out in accordance with the provisions of GB / T 30196-2013 Self-supporting Run-Flat Tire. After testing, the inner rubber dispersion grade was 8.6, the hardness was 70HA, there was no crack after 1.45 million fatigue tests, and the air permeability coefficient was 5.77×10 -14 m 2 ·s -1 The static pressure difference loss is within 3.23% / month, the compression heat generation is 20°C, and the compression deformation rate is 0.8%; after the inner rubber is applied to the tire, it can continue to travel 968 kilometers when the tire pressure is 0.

[0062] Example 4

[0063] A method for preparing an inner rubber of a run-flat tire comprises the following steps:

[0064] 10g of epoxy rubber was plasticized and put into an internal mixer together with 30g of brominated butyl rubber 3745, 1g of stearic acid, 1g of carbon nine resin and 1g of JJHM40 for mixing for 25s. Then 20g of nano carbon material SG06 and 30g of carbon black N660 were added and mixed to 90°C. The top plug was lifted and cleaned to 105°C, and the top plug was pressed again. When the mixing temperature reached 145°C, the top plug was lifted and the bottom plug was opened to discharge the glue. After standing for 4h and cooling to room temperature, the A-stage glue was obtained.

[0065] The stage A rubber, 30 g of low styrene butadiene rubber F1038, 2 g of zinc oxide, 1.2 g of accelerator DM, 0.3 g of accelerator TT, 0.4 g of sulfur, 0.5 g of insoluble sulfur and 0.8 g of alkylphenol disulfide were put into an internal mixer. When the mixture was mixed to 80° C., the top plug was lifted for cleaning and then pressed. When the mixing temperature reached 100° C., the top plug was lifted and the bottom plug was opened for rubber removal. After cooling to room temperature, a finished inner rubber was obtained.

[0066] The inner rubber performance test was carried out in accordance with the provisions of GB / T 30196-2013 Self-supporting Run-Flat Tire. After testing, the inner rubber dispersion grade was 8.9, the hardness was 72HA, there was no crack after 1.45 million fatigue tests, and the air permeability coefficient was 5.28×10 -14 m 2 ·s -1 The static pressure difference loss is within 3.12% / month, the compression heat generation is 20°C, and the compression deformation rate is 0.7%; after the inner rubber is applied to the tire, it can continue to travel 995 kilometers when the tire pressure is 0.

[0067] Comparative Example 1

[0068] It is prepared by adopting a conventional inner rubber formula and a mixing process. The specific formula is: 40g of brominated butyl rubber, 45g of natural rubber, 7g of MCSM, 10g of reclaimed rubber, 50g of carbon black N660, 15g of filler, 4g of leveler, 2g of stearic acid, 4g of resin, 11g of softener oil, 1.2g of sulfur, 1.5g of accelerator and 4g of zinc oxide.

[0069] The inner rubber performance test was carried out in accordance with the provisions of GB / T 30196-2013 Self-supporting Run-Flat Tire. After testing, the inner rubber dispersion grade was 7, the hardness was 50HA, there was no crack after 850,000 fatigue tests, and the air permeability coefficient was 7×10 -14 m 2 ·s -1 , static pressure difference loss is within 6% / month, compression heat generation is 30°C, and compression deformation rate is 7%; after applying the inner rubber to the tire, it can continue to travel 210 kilometers when the tire pressure is 0.

[0070] In summary, the dispersion grade of the inner rubber prepared in the embodiment of the present application can stably reach 8.5 (the full score of the carbon black dispersion tester is set to 10) or above, and the air permeability coefficient can be controlled within 5×10 -14 m 2 ·s -1 Below, the fatigue performance of the rubber (flexure test) can reach 1.4 million times without cracks, the static pressure difference loss is within 3.5% / month, the fatigue heat generation in the compression heat generation test is below 22°C, and the compression deformation rate is within 1%. Compared with the same type of conventional inner rubber, the present application can greatly improve the modulus and flexural performance of the inner rubber, while reducing the heat generation of the rubber. After the inner rubber of the present application is applied to the tire, the tire can continue to travel for more than 900 kilometers at 0 air pressure, while the same type of tire can only travel 100 to 300 kilometers at 0 air pressure. The inner rubber of the present application can greatly improve the mileage of the tire in the case of lack of air.

[0071] The above description is only an optional embodiment of the present application, and does not limit the patent scope of the present application. All equivalent structural transformations made using the contents of the present application specification under the inventive concept of the present application, or direct / indirect application in other related technical fields are included in the patent protection scope of the present application.

Claims

1. A run-flat tire inner rubber, characterized in that: By weight, it includes the following components: 30-50 parts of brominated butyl rubber, 30-40 parts of low styrene styrene butadiene rubber, 10-20 parts of epoxy rubber, 20-40 parts of nano-carbon material, 30-50 parts of carbon black, 2-5 parts of zinc oxide, 1-3 parts of stearic acid, 2-5 parts of tackifier, 1-2 parts of homogenizer, 0.5-1 parts of cross-linking agent and 1.4-2 parts of accelerator.

2. The inner rubber of the run-flat tire according to claim 1, characterized in that: By weight, the components include: 40 parts of brominated butyl rubber, 35 parts of low styrene butadiene rubber, 15 parts of epoxy rubber, 30 parts of nano carbon material, 40 parts of carbon black, 4 parts of zinc oxide, 2 parts of stearic acid, 3 parts of tackifier, 2 parts of homogenizer, 0.8 parts of crosslinking agent and 1.8 parts of accelerator.

3. The inner rubber of the run-flat tire according to claim 1 or 2, characterized in that: The component further comprises 0.5 to 1 part of alkylphenol disulfide by weight.

4. The inner rubber of the run-flat tire according to claim 1, characterized in that: The tackifier is one of C5 resin and C9 resin.

5. The inner rubber of the run-flat tire according to claim 1, characterized in that: The homogenizer is a mixture of one or more of RH100, CJ400 and JJHM40.

6. The inner rubber of the run-flat tire according to claim 1, characterized in that: The cross-linking agent is one of sulfur and insoluble sulfur or a mixture of the two.

7. The inner rubber of the run-flat tire according to claim 1, characterized in that: The accelerators include thiazole compounds and thiuram compounds.

8. The method for preparing the inner rubber of a run-flat tire according to any one of claims 1 to 7, characterized in that: The following steps are involved: The epoxy rubber is plasticized and then mixed with brominated butyl rubber, stearic acid, a tackifier and a homogenizer, and then nano carbon material and carbon black are added and mixed, and after rubber removal, a stage A rubber is obtained; The A-stage rubber is mixed with low-styrene styrene-butadiene rubber, zinc oxide, an accelerator, a crosslinking agent and alkylated disulfide, and after the rubber is discharged, a finished inner surface rubber is obtained.

9. The method for preparing the inner rubber of a run-flat tire according to claim 8, characterized in that: The step of plasticizing the epoxy rubber, mixing it with brominated butyl rubber, stearic acid, a tackifier and a homogenizer, adding nano carbon material and carbon black for mixing, and obtaining the A-stage rubber after rubber removal comprises: After plasticizing the epoxy rubber, put it into an internal mixer together with brominated butyl rubber, stearic acid, tackifier and homogenizer for mixing for 22s-28s, then put in nano-carbon material and carbon black and mix to 85℃-95℃, lift the top plug and clean to 100℃-105℃, then press the top plug, when the mixing temperature reaches 142℃-148℃, lift the top plug, open the lower top plug to discharge the rubber, and cool to room temperature to obtain stage A rubber.

10. The method for preparing the inner rubber of a run-flat tire according to claim 8, characterized in that: The step of mixing the A-stage rubber with low styrene butadiene rubber, zinc oxide, an accelerator, a crosslinking agent and alkylated disulfide, and obtaining a finished inner rubber after rubber removal, comprises: The stage A rubber is put into an internal mixer together with low styrene butadiene rubber, zinc oxide, accelerator, crosslinking agent and alkylated disulfide. When the mixing temperature reaches 75°C-85°C, the top plug is lifted for cleaning and then the top plug is pressed. When the mixing temperature reaches 95°C-105°C, the top plug is lifted and the lower top plug is opened for rubber discharge. After cooling to room temperature, a finished inner rubber is obtained.